The rule of law and land disputes in Indonesia - Amzulian Rifai (Fakulti Undang - Undang, 2004)
This article discusses how essential it is for the rule of law to be applied, in order to protect land rights and to avoid land disputes in Indonesia. This is an analysis of the Indonesian laws dealing with the rule of law and how the rule of law is practiced under the Indonesian legal system. The concept of human rights in general, and how Indonesian laws accommodate these rights will be examined. It appears that a lack of the rule of law and the lack of protection toward human rights have led Indonesia into a situation of political uncertainty and into episodes of sporadic violence. Indonesia’s failure to implement the rule of law has contributed to ongoing land disputes. Under former President Soeharto, the rule of law only exists in theory, but in practice the government has failed to apply it. As a result there is a lack of confidence in legal institution including the court system